Reseña de Hawkins, J. (2004). On intelligence. - Ros Rodríguez, Silvia (Pragmalingüística, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Hawkins, J. (2004). On intelligence.